Play in (work)time - Tóth, Rita; Mitev, Ariel (Vezetéstudomány / Budapest Management Review, 2022)
Contemporary management literature considers play as an important and inevitable aspect of organizational life. Workplace play permeates work processes in different qualities, and this is also reflected in terms of working time. This study aims to explore the relationship between play and time in an organizational context, contrasting it with the quality of work. The authors sought to answers the question of how play and time co-organise the life of organizations and what connections can be discovered in the triad of work, time, and play. It can be concluded that play and time are inseparable concepts in organizations and that in work processes they can discover ever-deepening levels of (temporal) admission of play, based, in each case, on dominant beliefs about the quality of and relationship between play and work.